Plan estratégico para la compañía de transportes pesados ciudad de Valencia, periodo 2013-2016. - Guerra Vera, Mariuxi Veronica. (2012)
This research work is based on information from the Heavy Transport Company "Ciudad de Valencia", which was formed on January 27, 2006 and during these years has been working without a strategic direction, for that reason has not had a sustained development. Through the application of surveys to shareholders, customers and management of the company were possible to determine current conditions. Among its strengths are detailed that it is working legally and having a large number of shareholders, among its weaknesses have little credibility the actions of its leadership and poor economic development that has taken over the course of these years. The current leadership of the company is aware of the existing need for the implementation of a strategic plan that addresses the efforts of all stakeholders towards a specific objective, which is known and shared by all, and that may lead to long-awaited development of the company. To structure the company's strategic plan was necessary to begin defining its purpose and what it wants to be, that is the mission and vision, as well as establishing institutional principles that will be the solid foundation on which rests the philosophy of the company. The company is divided into the following management areas: Social, Financial and Administrative policies were created routed the actions of each towards the achievement of the objectives, among which prioritized the signing of agreements to improve welfare of shareholders, strengthen credibility and confidence in the financial accounting management and promote a culture of strategic planning. To implement the proposed strategic plan was drawn up a budget that details an investment of $ 1400 for the first year, $ 4900 for the second year, $10900 for the third year and for the last year the investment amounts to $ 2900.